2017
DOI: 10.24200/sci.2017.4523
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Chronic Feeding with Food Azo Dyes on Drosophila melanogaster Oregon R

Abstract: Abstract. Arti cial azo dyes are widely used as coloring agents for foodstu s, drugs, and cosmetics. In this study, the toxic e ects of four di erent synthetic food dyes (Ponceau 4R, Sunset Yellow, Amaranth, Tartrazine) on 72 4h larvae of Oregon (R) wild type of Drosophila melanogaster were investigated. In addition, depending on chronic feeding, the life span of the ies was determined. For this purpose, six di erent concentrations of food dyes (5,10,15,20, 25, and 30 mg mL 1 ) were selected by preliminary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…(TURKOGLU et al, 2015) published that the longevity of Drosophila melanogaster decreased significant, depend on the different concentrations of Ponceau 4R. (UYSAL et al, 2017) notified that maximum mean life of Oregon R wild of D. melanogaster larvae at 72±4 hours decreased in different concentrations of Ponceau 4R depend on feeding. These studies data are compatible and supports the results of the study.…”
Section: Resultsmentioning
confidence: 99%
“…(TURKOGLU et al, 2015) published that the longevity of Drosophila melanogaster decreased significant, depend on the different concentrations of Ponceau 4R. (UYSAL et al, 2017) notified that maximum mean life of Oregon R wild of D. melanogaster larvae at 72±4 hours decreased in different concentrations of Ponceau 4R depend on feeding. These studies data are compatible and supports the results of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Uysal & Semerdöken (Uysal H. 2011) re-ported increased toxicity in Oregon R of Drosophila larvae (72±4 hours) depending on the increase in concentration of Pea green, whereas Semerdoken (Semerdoken 2012) is-sued that Tartrazine increased the mortality rate in Oregon R wild and Vestigial mutant strains of Drosophila larvae at 72±4 hours and Uysal et al (Uysal, Genç, and Ayar 2017) reported that, according to larval mortality and life span, Tartrazine had the highest toxicity in Oregon R wild of D. melanogaster larvae at 72±4 hours among other food dyes, Turkoglu et al (Türkoğlu, Benli, and Şahin 2015) notified that Brilliant Blue FCF caused the biggest decreased in life span of Drosophila melanogaster among other food colorants and Kumar et al…”
Section: Discussionmentioning
confidence: 99%
“…Turkoglu et al (2015) published that the longevity of Drosophila melanogaster decreased significantly, depending on the different concentrations of Ponceau 4R. Uysal et al (2017) notified that maximum mean life of Oregon R wild of D. melanogaster larvae at 72±4 hours decreased in different concentrations of Ponceau 4R depend on feeding. The researches data are compatible and supports the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study result is consistent with the researches below, where the toxic effects of Pea green (Tartrazine-E 102 and Brilliant Blue FCF-E 133 combination) are examined. Uysal & Semerdöken (2011) reported increased toxicity in Oregon R of Drosophila larvae (72±4 hours) depending on the increase in concentration of Pea green, whereas Semerdoken (2012) issued that Tartrazine increased the mortality rate in Oregon R wild and Vestigial mutant strains of Drosophila larvae at 72±4 hours and Uysal et al (2017) reported that, according to larval mortality and life span, Tartrazine had the highest toxicity in Oregon R wild of D. melanogaster larvae at 72±4 hours among other food dyes, Turkoglu et al (2015) notified that Brilliant Blue FCF caused the biggest decreased in life span of Drosophila melanogaster among other food colorants and Kumar et al (2019) revealed that on exposure to Brilliant Blue, larvae and pre-adult stages were prone to developmental toxicity.…”
Section: Discussionmentioning
confidence: 99%